Totally submerged deciduous maxillary molar - Janas-Naze, Anna; Osica, Piotr (Journal of Education, Health and Sport, 2018)
The total reimpaction of deciduous teeth is becoming more and more common, even though few cases have been reported in the literature. The condition most often affects the mandibular second deciduous molar and the maxillary first deciduous molar least often. A case of totally submerged maxillary deciduous molar in a 11 year old girl is described,.